Design and finite element analysis of a portable bus service ramp to reduce dependence on service pits - Novian Dhamas Ramadhan; Muhammad Alfarizi; Agus Widyianto (Journal of Automotive and Mechanical Applied Technology, 2025)
This study aims to: (1) design and analyze a portable ramp to improve bus repair efficiency at PT. United Tractors Semarang Branch, (2) with a focus on facilitating repairs and reducing dependence on service pits. (3) This portable ramp is expected to overcome access constraints to the underside of buses, speed up repair time, and improve work safety for mechanics. This study uses the DMADV (Define, Measure, Analyze, Design, Verify) method to develop portable ramps. These stages include problem discovery, technical data collection, analysis of materials, 3D model design using SolidWorks, and verification using Finite Element Analysis (FEA) to ensure structural strength and compliance with safety standards. This study successfully designed and analyzed a portable ramp for bus repairs, capable of withstanding an operational load of 88,750 Newtons with a safety factor≥ 3.0, a maximum deformation of ≤ 5 mm, and a safe von Mises stress distribution. The selection of ASTM A36 Carbon Steel resulted in optimal strength and weight, as well as cost efficiency. The ramp design also meets workshop operational needs and improves repair process efficiency. This research successfully designed an optimal portable ramp for the PT. United Tractors Semarang Branch Workshop, considering operational efficiency and safety, ASTM A36 Carbon Steel was selected as the best material based on strength, weight, and cost. It is recommended to implement this portable ramp, along with technician training, maintenance system development, and expansion to other branches, to improve bus repair efficiency.